Regional assemblage and the spatial reorganisation of health and care: the case of devolution in Greater Manchester, England. Issue 7 (13th February 2019) - Lorne, Colin; McDonald, Ruth; Walshe, Kieran; Coleman, Anna
Abstract: In this paper, we examine how space is integral to the practices and politics of restructuring health and care systems and services and specifically how ideas of assemblage can help understand the remaking of a region. We illustrate our arguments by focusing on health and social care devolution in Greater Manchester, England. Emphasising the open‐ended political construction of the region, we consider the work of assembling different actors, organisations, policies and resources into a new territorial formation that provisionally holds together without becoming a fixed totality. We highlight how the governing of health and care is shaped through the interplay of local, regional and national actors and organisations coexisting, jostling and forging uneasy alliances. Our goal is to show that national agendas continued to be firmly embedded within the regional project, not least the politics of austerity. Yet through keeping the region together as if it was an integrated whole and by drawing upon new global policy networks, regional actors strategically reworked national agendas in attempts to leverage and compete for new resources and powers. We set out a research agenda that foregrounds how the political reorganisation of health and care is negotiated and contested across multiple spatial dimensions simultaneously.